Legal and Ethical Issues Regarding Minors in the Italian Coronavirus Flu Emergency - Fedeli, Piergiorgio; Cannovo, Nunzia; Scendoni, Roberto; Cingolani, Mariano (Frontiers in Pediatrics, 2021)
On February 21, 2020, Italy became one of the countries hit by an epidemic of the new coronavirus that causes “severe acute respiratory syndrome coronavirus 2” (SARS-CoV-2). Even a month before that, however, the Italian government began issuing a series of decrees and ordinances aimed at the containment of the virus in Italy, the first of them on January 25, 2020. The COVID 19 infection has been faced as an epidemic through measures to enforce a high degree of isolation. These regulations hold for minors, as well, with consequent difficulties for this age group. While at the moment young people appear to be the least vulnerable to the severe complications of COVID 19, the psychological problems that may be brought on by pandemic-related restrictions should be taken into serious consideration.